Using a Geographical Information System to investigate the relationship between reported cryptosporidiosis and water supply - Hughes, Sara (BioMed Central, 2004)
BACKGROUND: This paper reports on a study investigating the epidemiology of sporadic cryptosporidiosis in the North West of England and Wales using a Geographical Information System (GIS) to map location of residence of cases. Some 747 reports of cases were made to CDSC North West of which 649 reports were suitable for analysis. Cases were plotted on the maps of water supply zone and water quality area boundaries, provided by the two main water utilities. RESULTS: It was notable that there were major spatial variations in attack rate across the North West and Wales. The most dramatic example was the large difference between the Greater Manchester conurbation with many reports and Liverpool with none. Given the distribution of previously detected waterborne outbreaks in the region it was initially thought that drinking water source may be an explanation. However, an analysis of the distribution of cases in the Greater Manchester area showed no correlation with any of five water supplies that serve the conurbation. CONCLUSIONS: Our study has shown a dramatic variation in the incidence of laboratory confirmed cryptosporidiosis within two regions of the United Kingdom. Further analysis has not been able to prove drinking water as a likely explanation of this variation which so far remains unexplained.